Freedom of Expression and the Media: A Case-study from The Netherlands - Snel, Drs. Johan (Žurnalistikos tyrimai, 2015)
There is “no such thing as free (non-ideologically constrained) speech; no such thing as a public forum purged of ideological pressures or exclusions”. Stanley Fish’s famous thesis (1994) is illustrated by this case study on the public debate on freedom of expression in the Netherlands during the first decade of the 21st century. Far from serving tolerance or minority rights, as originally intended, it produced a whole line of argumentation that have excluded many from the public debate and filled it with a more exclusive content, especially regarding religion in general and Muslims in particular. A renewed identification with the toleration discourse would help the media in regaining their public role and will be helpful for journalists covering the debate.